1983
DOI: 10.1115/1.3254546
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Lubrication of Finite Slider Bearings: Effect of One Dimensional Film Shape, and Their Computer Aided Optimum Designs

Abstract: The effect of the film shape on the load carrying capacity of a hydrodynamically lubricated bearing has not been considered an important factor in the past. Flat-faced tapered bearing and the Raileigh’s step bearing of constant film thickness have been the primary forms of film shapes for slider bearing studies and design data developments. This article, by the computer aided numerical solution of the Reynolds equation for two dimensional incompressible lubricant flow, investigates hydrodynamically lubricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Various 3D meshes of nondimensional pressure distribution are shown from Figures 3 , 4 , 5 , 6 , and 7 . The results generated by the researchers [ 17 , 18 ] are closely matching the path with grid size of 4 × 4, 8 × 8 and so forth. The results computed by [ 12 ], with the limited grid size of 9 × 9, are also showing good agreement with the present higher order grid size.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Various 3D meshes of nondimensional pressure distribution are shown from Figures 3 , 4 , 5 , 6 , and 7 . The results generated by the researchers [ 17 , 18 ] are closely matching the path with grid size of 4 × 4, 8 × 8 and so forth. The results computed by [ 12 ], with the limited grid size of 9 × 9, are also showing good agreement with the present higher order grid size.…”
Section: Resultsmentioning
confidence: 62%
“…The authors have reported that the increase in pressure is more for the exponential and hyperbolic sliders [ 16 ]. Moreover, investigators [ 17 , 18 ] have studied the THD behavior of a slider bearing having a pocket and reported that the maximum pressure is higher for the pocketed bearing in comparison to plane slider bearing. [ 19 , 20 ] studied the influence of film shape on the performance of longitudinally rough, infinitely wide slider bearing for isothermal conditions and reported better load carrying capacity with exponential, secant, and hyperbolic film shapes in comparison to the inclined plane film shape.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of finite bearing width is an old one, first analyzed by Michell (6). With the addition of rotary geometry as here, the problem was addressed numerically by Gregory and Maday (7), and a representative review of the literature is given by Bagci and Singh (8). Their results show that a taper bearing of width 2 L (the situation of 1 of the 1.3 bearings, if the rotation is ignored) achieves some 72 to 74% of its infinite‐width load capacity in the range d 1 / d 2 = 1.6 to 3.0, which corresponds to d 2 = 83.3 to 25 μm here.…”
Section: Discussionmentioning
confidence: 99%
“…By integrating equation (6) twice and considering equation (2) as well as the boundary conditions, at…”
Section: Reynolds Equation For a Scotch Yoke Linear Bearingmentioning
confidence: 99%